El Siglo XX. - González Blackaller, Ciro E.; Guevara Ramírez, Luis (México, D.F. : Editorial Herrero, 1975)
Presenta un estudio sobre los principales acontecimientos que caracterizaron al Siglo XX en el mundo.
Keywords: HISTORIA; SIGLO XX